MATHEMATICAL MODELING OF THE SEQUENCE OF MACHINING SECTIONS OF COMPLEX SURFACES WHEN MILLING ON A TRIAXIAL CNC MACHINE TOOL (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The idle running times of the working units of a machine tool are the sum of the idle running times for the tool change and for changing the area uder treatment. The paper presents mathematical models, establishing the relationship between the additional time for performing the technological operations with the parameters of both the technological equipment and the object under treatment. The mathematical models for minimizing the idle moves when a tool passes from one machined section to another, allows to reduce the additional treatment time, which, in turn, leads to an increase in the productivity of the process of actual milling.